ETB2 receptor subtype stimulation relaxes the iris sphincter muscle - Rocha-Sousa, A; Saraiva, J; Amaral, M; Alves-Faria, P; Falcao-Reis, F; Leite-Moreira, A. F (Physiological research, 2009)
Effects of ETB receptor stimulation and its subcellular pathways were evaluated in carbachol pre-contracted rabbit iris sphincter muscles (n=51). ETB stimulation with sarafotoxin (SRTX-c; 10-10-10-6 M) was tested in the absence (n=7) or presence of 10-5 M of: BQ-788 (ETB2 receptor antagonist; n=6), L-NA (NOS inhibitor; n=7) or indomethacin (cyclooxygenase inhibitor; n=10). Effects of ETB stimulation by endothelin-1 (ET-1; 10-10– 10-7 M) in the presence of an ETA receptor antagonist (BQ-123; 10-5 M; n=7) and of ETB1 stimulation by IRL-1620 (10-10–10-7 M; n=7) were also tested. Finally, the effects of SRTX-c (10-9–10-7 M) in electric field stimulation (EFS) contraction were evaluated (n=7). ETB receptor stimulation by SRTX-c or ET-1 in presence of BQ-123 promoted a concentration-dependent relaxation of the rabbit iris sphincter muscle by 10.8±2.0 % and 9.4±1.8 %, respectively. This effect was blocked by BQ-788 (-2.3±2.0 %), L-NA (4.5±2.3 %) or indomethacin (2.3±2.9 %). Selective ETB1 stimulation by IRL-1620 did not relax the iris sphincter muscle (0.9±5.4 %). EFS elicited contraction was not altered by SRTX-c. In conclusion, ETB receptor stimulation relaxes the carbachol precontracted iris sphincter muscle, an effect that is mediated by the ETB2 receptor subtype, through NO and the release of prostaglandins.
Keywords: Endothelin-1; Carbachol; Prostaglandins; Oligopeptides; receptor endotelinu B; Electric Stimulation; Dose-Response Relationship, Drug; nitroarginin; receptor endotelinu A; Prostaglandin-Endoperoxide Synthases; oxid dusnatý; financování organizované; endotelin-1; cyklooxygenasy; synthasa oxidu dusnatého; Muscle, Smooth; Financing, Organized; zvířata; Nitric Oxide; Iris; oligopeptidy; Endothelins; peptidy; Piperidines; indomethacin; Peptides; hladké svalstvo; relaxace svalu; Peptide Fragments; Male; Receptor, Endothelin A; Receptor, Endothelin B; karbachol; iris; prostaglandiny; Indomethacin; Nitroarginine; peptidové fragmenty; králíci; inhibitory enzymů; vztah mezi dávkou a účinkem léčiva; piperidiny; Animals; elektrická stimulace; mužské pohlaví; endoteliny; Muscle Relaxation; Enzyme Inhibitors; Rabbits; Nitric Oxide Synthase